Evaluation of Bowel Function on Patient Post Operative Hirschsprung Disease - Faradiba, Ailsa Reina; Athiyyah, Alpha Fardah; Hariastawa, I Gusti Bagus Adria (Universitas Airlangga, 2023)
Highlights:1. All HD patients have good defecation quality after surgery.2. Almost all HD patients can control bowel movements without constipation or social problems after surgery.3. The most common problem patients face after surgery is soiling, which sometimes requires diapers. AbstractIntroduction: Hirschsprung's disease (HD) is a congenital disease in which Meissner and Auerbach's plexus ganglion cells are lost on the distal side of the digestive tract, thus interfering with defecation. The postoperative defecation process was assessed to describe the patient's quality of life. This study aimed to describe the quality of defecation in pediatric HD patients after surgery. Methods: This was a descriptive study on pediatric PD patients who received surgery in Dr. Soetomo General Academic Hospital, Surabaya, from 2018 to 2021. Demographic data came from Dr. Soetomo General Academic Hospital, Surabaya. The incontinence evaluation was assessed using the Rintala Score.Results: A total of 14 pediatric HD patients underwent definitive surgery and had good scores on the Rintala score. There were 2 (14.3%) patients with maximum scores, 6 (42.9%) patients with normal scores, and 6 (42.9%) patients with good scores. The highest distribution in patients was always being able to hold bowel movements (81.8%), uncertain in reporting the desire to defecate (40.9%), 1-2 times a day (68.2%), never dirty (54.5%), never constipated (77.3%), and had no social problems (77.3%).Conclusion: Pediatric HD patients had a good outcome after a definitive operation. The most common demographics with high satisfaction rates were male and female patients with normal nutritional status, above one-year-old, normal birth weight, and term labor.